Metode Pembelajaran Efektif dan Efisien - Sobri, Hanif; Saida Rahma, Fathati; Larasati, Dewi (STAIN Bengkalis, 2022)
Some Arabic teachers complain about their role as Arabic teachers and the ineffectiveness of learning in the classroom. Among the things that can cause are: Teachers don't know the concept of effective and efficient learning, how to streamline learning and organize effective learning. As a result, learning is only done by transfer of knowledge (knowledge transfer) the importance in learning, especially Arabic language teachers, to find out how to make the learning more effective.